Intention to have a third child among millennial parents with two children in eastern China: A cross‐sectional survey - Fen Xu; Shen‐jun Jiang; Pan‐pan Ge; Jue Yang; Sha Lu (Wiley, 2024)
Abstract Aim This Study Aimed to Assess the Intention to Have a Third Child among Millennial Parents (25-40 years old) with Two Children in a City in Eastern China and to Explore the Influencing Factors Related to Fertility Intention. Design A cross‐sectional design study. Methods A convenience sampling method was used to enrol participants of childbearing age who visited two tertiary hospitals in Hang zhou, a city in eastern China, from June 2021 to March 2022. We conducted a face‐to‐face questionnaire survey with 520 participants and calculated the prevalence of intention‐related factors. Multivariate logistic regression was used to analyse the independent influencing factors of fertility intention. Results In total, 105 (20.2%) participants had the intention to have a third child. The results showed that 'employment status', 'age', 'reasons for wanting a third child', the considered 'biggest barrier to having a third child', 'views on the three‐child policy', 'desired free services', 'supporting work policies' and 'assistance policies' were significant independent influencing factors of intention to have a third child (p‐value < 0.05). The intention of the participants 'over 30 years old' was 2.466 times that of those '30 years old and under', and 'older age/personal health status' was considered the 'biggest barrier to having a third child'. Regarding policy and social reasons, the participants who need 'medical assistance' policy negatively affect the intention to have a third child (OR = 0.453, 95% CI = 0.247-0.830). Implications for Healthcare/Nursing Nursing plays an important role in health promotion. Nurses can help couples make wise decisions about fertility by providing professional consultation, education, evaluation and support. They can also provide corresponding nursing and guidance to improve couples' health quality and overall reproductive success. Conclusions The general level of intention to have a third child of Millennial parents with two children is still low. The participants who are 'housewives/househusbands', 'over 30 years old', and satisfied with the state of 'medical assistance' have higher fertility intentions. Patient or Public Contribution It is particularly meaningful for the policymakers to improve the social support system and raise universal awareness to encourage childbirth.